De l’expérience formatrice à l’expérience apprenante : genèse et perspectives pour une mise en récit d’un processus de professionnalisation - Lucie Roger; Anne Jorro; Philippe Maubant (Éducation et Socialisation)
The different situations encountered by a professional make up the frame of the analysis of the working activity. These situations are analyzed as learning potentiality and as development of the workers and learners. We hypothesize that different situations are to be mobilized to rethink a personal and professional route whose finality is learning and development of the worker. These situations have to be thinking like a set of opportunities to learn and to grow, in other words, as carriers of formative experiences situations. These encounter of situations could taking sens by a dialogical process or dialectic established between different situations. To support this thesis, we propose to identify and characterize these carriers learning and development situations. To do this, we propose to appeal to the experiential posture of these different situations, especially some of them, which are considered to be representative and often iconic vocational training, that is to say training period.